1944
DOI: 10.1152/ajplegacy.1944.142.5.648
|View full text |Cite
|
Sign up to set email alerts
|

The Renal Reabsorptive Mechanism for Inorganic Phosphate in Normal and Acidotic Dogs

Abstract: Phosphate plays a role in a number of body functions: calcium phosphat'e is a prominent constituent of skeletal structures; organic phosphate complexes are of importance in energy transformations within cells; and, as the chief buffer component of the urine, inorganic phosphate aids the body in balancing its acid base requirements. Since the urine is the major portal of exit for excess phosphate of dietary origin, the renal mechanisms controlling loss or conservation of the body's stores of inorganic phosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
1
2

Year Published

1947
1947
1973
1973

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(73 citation statements)
references
References 7 publications
7
63
1
2
Order By: Relevance
“…There appears from our limited data to be no difference between this maximum rate of reabsorption in acidosis and under conditions of normal acid-base balance. In this respect, results on man and dog (12) are in agreement. In contrast, at normal plasma concentrations of phosphate the reabsorption of phosphate is significantly less complete in acidosis than under conditions of normal acid-base balance.…”
Section: The Relation Between the Quantity Of Phosphate Filtered Thsupporting
confidence: 73%
See 2 more Smart Citations
“…There appears from our limited data to be no difference between this maximum rate of reabsorption in acidosis and under conditions of normal acid-base balance. In this respect, results on man and dog (12) are in agreement. In contrast, at normal plasma concentrations of phosphate the reabsorption of phosphate is significantly less complete in acidosis than under conditions of normal acid-base balance.…”
Section: The Relation Between the Quantity Of Phosphate Filtered Thsupporting
confidence: 73%
“…Accordingly, the spontaneous rate of excretion of phosphate is higher in acidosis, a factor no doubt of major importance in explaining the phosphaturia in man. In our experience dogs show much less phosphaturia and no appreciable change in reabsorption of phosphate at normal plasma levels in acidosis (12). In these observations on man there appeared to be no significant effect of acidosis on plasma phosphate concentration, the range of variation being about the same in acidosis as in the normal.…”
Section: The Relation Between the Quantity Of Phosphate Filtered Thsupporting
confidence: 41%
See 1 more Smart Citation
“…Certain published data, however, fail to support this thesis (27,34,35) and in our own studies we have been unable to detect any significant change in the various moieties of total blood phosphorus either in sivo or in vitro as a consequence of parathyroid extract administration. Harrison and Harrison (27) and Pitts and associates (36,37) have suggested that a renal tubular maximal capacity for phosphorus reabsorption (TmP) exists. This maximal capacity or "threshold" value is presumed to be directly under the influence of the parathyroid glands.…”
Section: Fig 4 the Immediate Effects Of Abrupt Increases In Phosphomentioning
confidence: 99%
“…Then either isotonic (0.9%) or hypertonic (2.5% or 5%) saline was used. Sodium clearances were calculated from plasma sodium levels, glomerular filtration rates and urinary sodium excretion rates (23). Plasma and urine sodium concentrations were determined by the methods of Bradbury (24) and Butler and Tuthill (25), respectively.…”
mentioning
confidence: 99%